Reconstructing 'True Convivencia': The Roles of Muwalladun Mozarab and Jews in Coexistence in Al-Andalus During the Golden Age of Umayyad and First Taifa Periods - Mohammad Nor Bin Zaidi (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This article investigates the unique interaction between three social groups; Muwalladun, Mozarabs and Jews, that lived together during Muslim Spain's era (732 CE-1492 CE) with the focus on unravelling the socio-cultural mechanism behind this interaction which led to the culmination of an interesting period known as "la Convivencia”. Viewing this topic through socio-cultural lenses, this article considers this approach the best method to understand Muwalladun, Mozarabs and Jews' interaction by assessing them as undergoing the process of acculturation and assimilation. This article aims to address the scholarly gap which, due to the lack of socio-cultural perspective of La Convivencia, led to some scholars denying the existence of this period. The presence of diverse communities in al-Andalus created multiple variables that pushed for coexistence like the emergence of new social groups, Muwalladun, which were affected by the influence of dominant Arabic culture and increased their rapid conversion to Islam due to equal opportunities for social mobility as Muslims. In addition, a similar role was exercised by Mozarabs, who built a connection with the brothers in faith in northern Iberia, spreading their tolerant attitude and knowledge gained in the south through trade and immigration. As for Jews, they benefited tremendously from this interaction; with the Muslims as the model and benchmark, their society prospered and flourished to the point of creating the Jewish Golden Age.